Hypersensitivity reaction to hyaluronic acid dermal filler after COVID-19 vaccination: A series of cases in São Paulo, Brazil - Luciena Cegatto Martins Ortigosa; Fabiano Carvalho Lenzoni; Maria Victória Suárez; Artur Antônio Duarte; Luiz Euribel Prestes-Carneiro (International Journal of Infectious Diseases, 2022)
Brazil ranked second in the world for the number of aesthetic procedures carried out in 2019. Five case reports of delayed hypersensitivity reaction to hyaluronic acid dermal filler after COVID-19 vaccination are presented in this paper. Additional vaccination for new variants, including omicron, will be necessary; therefore, aesthetic professionals should be aware of this possibility and advise patients accordingly.